AGENDA & MINUTES GENERAL COUNCIL MEETING OF IAPSM UPUK - Editor, Chief (Indian Journal of Community Health, 2016)
AGENDA & MINUTES GENERAL COUNCIL MEETING OF IAPSM UPUK Department of Community Medicine, SRMS IMS, Bareilly. (15th Oct’ 2016; 05:00 PM to 06:30 PM)